PTH-263 Analysing short-term outcomes and patient satisfaction with laparoscopic ventral mesh rectopexy. (22nd June 2015) - Lo, T; Welman, T; Nisar, P; Trivedi, P; Bearn, P
Abstract : Introduction: Laparoscopic ventral mesh rectopexy (LVMR) has been used to treat rectal prolapse and obstructive defaecation syndrome (ODS). However, limited outcome data have been reported. The purpose of this study was to evaluate the indications and outcomes of LVMR by comparing pre-and postoperative function and quality of life. Method: A Prospective database identified all patients undergoing from November 2011 to July 2014. Cleveland clinic constipation score (CCCS), St Mark's incontinence score (SMIS), Quality of life SF12 (QOL) and Cleveland surgery satisfaction questionnaire were used to evaluate surgical outcomes and patient satisfaction retrospectively. Results: 28 LVMRs (26 women, mean age +/− SD, 69 +/− 29 years, median 65 years), were performed during the study period. 25 patients were followed up (median 71 days, range 39 to 197 days). 78% of patients responded to the questionnaire with 15 patients suffered from rectal prolapse and 7 patients ODS). Eight patients underwent LVMR following perineal repair, of these 1 reported recurrence of prolapse and faecal leakage. The mean score for CCCS and SMIS were compared pre and post-operatively. Both showed a reduction in symptoms, scoring 11.0 vs. 7.0 (P < 0.0003) and 12.0 vs. 7.8 (P < 0.0001) respectively. Changes in physical component and mental component summary were observed using QOL SF-12 with no statistically significance and a mean difference of 4.02 and 5.68. 82% of patients completing the Cleveland surgery satisfaction questionnaire would recommend LVMR with a mean score of 4.3 out of 5. Conclusion: LVMR is associated with low recurrence and a significant improvement in symptoms of pelvic floor dysfunction. Improvement in QOL was observed with the majority of patients recommending this procedure. Disclosure of interest: None Declared.